Thermal Decomposition of a Mixture of Tar with Primary Coal Tar with the Additives of Iron Compounds - Baikenov, M. I.; Kochegina, E. V.; Khalikova, Z. S.; Absat, Z. B.; Karimova, A. B.; Rakhimzhanova, N. Zh.; Tusipkhan, A.; Baikenova, G. G. (Solid Fuel Chemistry, 2019)
Studies on the thermal destruction of a mixture of vacuum residue (tar) and primary coal tar (PCT) with and without Fe3O4 and β-FeOOH catalytic additives, which were performed using thermogravimetry and differential scanning calorimetry in an inert atmosphere at a heating rate of 10 K/min, are reported. Based on the results of thermogravimetric analysis and the kinetic parameters of the process, activation energies were calculated, and these activation energies can be used in the development of methods for the technological calculation of reactors and the selection of construction materials for their manufacture.
Keywords: primary coal tar; tar; destruction; nanocatalytic additive